PR status is a more decisive factor in efficacy of adding pertuzumab into neoadjuvant therapy for HER2-positive and lymph node-positive breast cancer than ER status: a real-world retrospective study in China - Liu, Xiaoyu; Liu, Zhaoyun; Li, Chao; Song, Xiang; Wang, Xinzhao; Li, Sumei; Yu, Zhiyong (World journal of surgical oncology, 2023)
Background Although neoadjuvant trastuzumab and pertuzumab (HP)-based regimens are recommended for human epidermal receptor-positive (HER2 +)/lymph node-positive (N +) breast cancer (BC) patients according to NCCN guidelines, it is undeniable that many patients achieved pathological complete response (pCR) after trastuzumab (H)-based regimens without adding pertuzumab to treatment. Patients who specifically benefit from pertuzumab must be identified. The aim of this retrospective study was to evaluate progesterone receptor (PR) status as a predictor of response to the addition of pertuzumab in HER2 + /N + breast cancer. Methods One hundred forty-two patients who were diagnosed as HER2 + /N + BC without distant metastasis and followed by neoadjuvant HP-based or H-based therapy were retrospectively included. The endpoints were pCR and disease-free survival (DFS) times. Results In total, the pCR occurred in 25 of 87 patients (28.74%) in group H compared with 32 of 55 (58.18%) in group HP. The results revealed that hormone receptor (HR) status was significantly different on pCR in group HP. The odds of pCR for patients who have HR-positive tumors were 0.160 times (P = 0.011) that for patients with HR-negative tumors by multivariable analysis. Moreover, a similar probability of PR-positive (PR +) patients, whatever estrogen receptor (ER) status was, achieving pCR in group HP was observed. The ROC curves showed different anti-HER2 regimens provide worst predictive value in the PR + cohort (N = AUC = 0.521, 95% CI: 0.348-0.694, P = 0.813) compared with the overall cohort (AUC = 0.644, 95% CI: 0.550-0.738, P = 0.004) and ER + cohort (AUC: 0.559, 95% CI: 0.405-0.713, P = 0.451). And PR status (AUC = 0.760, 95% CI: 0.626-0.894, P = 0.001) had a greater predictive value than ER status (AUC = 0.658, 95% CI: 0.508-0.807, P = 0.048) in group HP. DFS analyses were done on 141 patients. Although ER and PR status did not show significant difference in group HP (P = 0.789 and 0.088, respectively), HP-based therapy contributed to better DFS in the ER - and PR - cohorts (P = 0.035 and 0.015, respectively). Conclusions Compared with ER status, PR status might be a more valuable factor predicting the efficacy of adding pertuzumab into neoadjuvant therapy for HER2 + /N + BC. PR + patients benefit little from the addition of pertuzumab. Keywords: HER2-positive breast cancer, Progesterone receptor, Neoadjuvant therapy, Pathological complete response